ANALYSIS OF FIELD TRIALS ON THE SELECTION OF DISC HARROWS FOR SURFACE TILLAGE OF ROW CROPS - O.Mamadiyorov, N.Saidov, M.Xidirov, D.B.Irgashev (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The time for seedbed preparation in the transition period between crops is also very short, and it is based on the limited annual sunshine duration in the intensive rice wheat rotation area. Excessive residues in the field cause poor performance of soil-engaging tools, which affects the timely planting of the next crop. Therefore, agricultural producers have been seeking well adapted and high-performance tillage tools to deal with the problems of excessive crop residues for no-tillage seeding operations. Numerous types of soil-engaging tools are in use for conservation tillage, such as disc, hoe, chisel, and sweep for developing seed furrow and handling crop residues. For dense residues cover conditions, the conventional soil-engaging tools for conservation tillage are various rotary tools (e.g., vertical discs and disc coulters). Each rotary tool can be classified by its geometry, such as plain-type, notched-type, and rippled-type.